(untitled) (Journal of the Management Sciences, 2024)
The purpose of this study is two-fold. The first is to determine whether the financial performance of the microfinance banks is comparable with their commercial banks counterparts. The second is to determine whether the microfinance banks have met the targets set out in the Microfinance Policy. Descriptive research design was adopted for the study. Data on the financial performance of microfinance banks and the targets in the Microfinance Policy were obtained from the Central Bank of Nigeria while the financial performance of the commercial banks were extracted from the annual report and accounts of the individual banks. The data were analysed using means and standard deviation while t-test statistics was used to test whether there was difference in the return of the two groups of banks. Z-test of difference in proportion was used to determine whether the microfinance banks have met the targets in the Microfinance Policy with respect to proportion of credit to the economy and to the GDP. Findings show that the average return on equity of the microfinance banks is significantly higher than the average return of the commercial banks. Findings also show that there is no significant difference in the return on equity of the top 5 commercial banks and the top 5 microfinance banks. Furthermore, the study established that the microfinance banks have not met the targets on proportions of credit to the economy and proportion of credit to GDP. The implication of findings is that the anxiety over the financial viability of the microfinance banks do not have any economic justification. Findings also imply that except if additional policy measures are put in place, the targets in the Microfinance Policy to be attended in 2020 may not be realized.